Auditoria de gestión al área de producción y su incidencia en la rentabilidad de la empresa “tejidos homer”, cantón Quito, periodo 2012 - Borja Borja, Jennifer Valeria (2015)
This research project is a management audit of the production area and its impact on the profitability of the company fabrics Homer, Canton Quito, 2012 period, which has three objectives as follows: analyze the methods used to control the quality of the finished product, examine the level of trust inventory system, assess the degree of compliance with production schedules. To comply with the assessment given area an evaluation plan was structured following phases: preliminary phase of planning, evaluation planning, implementation, evaluation, report preparation, and delivery of results, methods and types of applied research that we use for the interpretation and analysis of the results, where the following findings were found: the company has a manual of internal policies, but employees are not evaluated periodically to verify whether there is compliance with them, the production schedule is performed on a monthly basis but not satisfied because it is modified according to the demand, the inventory of finished products is not organized for the most part, being a stock of long ago so it no longer knows for sure what that he is. The results obtained in the development of the research reflect the following: quality control of finished garments from fabrics company homer is efficient, but do not carry any written records, physical inventory verification it was found that the inventory finished products is exceeded garments contained in the orders delivered by disregard of the charge entering the models and sizes of the goods delivered is confused and you type the wrong name of the garment which results in excess clothing in inventories, evaluated the program began to verify that production does not fully comply with production schedules due to the delay of sending orders to the production area later this month.